A study on Hermite-Hadamard type inequalities for s-convex functions via conformable fractional integrals - SET, Erhan; GÖZPINAR, Abdurrahman (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In the present note, firstly we established a generalization of Hermite Hadamard’s inequality for s-convex functions via conformable fractional integrals which generalized Riemann-Liouville fractional integrals. Secondly, we proved new identity involving conformable fractional integrals via beta and incompleted beta functions.Then, by using this identity, some Hermite Hadamard type integral inequalities for s-convex functions in the second sense are obtained. Mathematics Subject Classification (2010): 26A33, 26A51, 26D10, 26D15.